Demographic and clinical variants of lichen planus: a retrospective study [Retracted Article] - Algaradi, Khaled Husein; Elkasah, Fathi; Bin Al-Zou, Amer (Sirte Journal of Medical Sciences, 2023)
Background: Lichen planus is a group of chronic inflammatory diseases affecting stratified squamous epithelia. Objective: To determine the demographic characteristics, the clinical variants, and the site involvement and to compare the study results with the findings of the literature. Materials and method: This study was based on the retrospective analysis of the medical files of patients who attended an two private clinics in Almansoora district, Aden, between the years of 2019 – 2020. SPSS 17 was used. Data were analyzed using descriptive statistics and chi-square test. P < 0.05 was considered statistically significant. Results: The study patients were 102 (62.2%) females and 62 (37.8%) males. The age ranged between 20 – 60 years. The age group 41 – 50 had the highest number of patients 56 (34.1%). The involvement of skin only was observed in (58.6%) patients. Concomitant involvement of mucous membranes with skin was seen in (16.3%) patients, nails with skin in (7.3%), face in (6.1%) and skin + mucous membranes + nail in (4.9%) patients. Penis involvement was found in (2.4%) male patients and scalp involvement in (2.4%) female patients. Classic variants of lichen planus were predominant in (63.4%) patients followed by hypertrophic lichen planus in (15.9%), and pigementosus lichen planus in (11.0%) patients (p = 0.001). Koebner phenomenon found in (18.3%) patients with lichen planus. The arterial hypertension found in (11.0%) patients followed by diabetes mellitus in (8.6%) patients and hepatitis c in (2.4%) patients. Conclusion: Most affected patients of lichen planus were the age group 41 – 50 years old, followed by the age group > 50 years old. Further studies are need to determine the prevalence of this skin disorders among residents of Aden governorate.